Remote Ischemic Preconditioning Acutely Improves Coronary Microcirculatory Function. Issue 19 (2nd October 2018) - Lau, Jerrett K.; Roy, Probal; Javadzadegan, Ashkan; Moshfegh, Abouzar; Fearon, William F.; Ng, Martin; Lowe, Harry; Brieger, David; Kritharides, Leonard; Yong, Andy S.
Abstract : Background: Remote ischemic preconditioning (RIPC) attenuates myocardial damage during elective and primary percutaneous coronary intervention. Recent studies suggest that coronary microcirculatory function is an important determinant of clinical outcome. The aim of this study was to assess the effect of RIPC on markers of microcirculatory function. Methods and Results: Patients referred for cardiac catheterization and fractional flow reserve measurement were randomized to RIPC or sham. Operators and patients were blinded to treatment allocation. Comprehensive physiological assessments were performed before and after RIPC/sham including the index of microcirculatory resistance and coronary flow reserve after intracoronary glyceryl trinitrate and during the infusion of intravenous adenosine. Thirty patients were included (87% male; mean age: 63.1±10.0 years). RIPC and sham groups were similar with respect to baseline characteristics. RIPC decreased the calculated index of microcirculatory resistance (median, before RIPC: 22.6 [interquartile range [IQR]: 17.9–25.6]; after RIPC: 17.5 [IQR: 14.5–21.3]; P =0.007) and increased coronary flow reserve (2.6±0.9 versus 3.8±1.7, P =0.001). These RIPC‐mediated changes were associated with a reduction in hyperemic transit time (median: 0.33 [IQR: 0.26–0.40] versus 0.25 [IQR: 0.20–0.30]; P =0.010). RIPC resulted in a significant decrease in the calculated index of microcirculatory resistance compared with sham (relative change with treatment [mean±SD] was −18.1±24.8% versus +6.1±37.5; P =0.047) and a significant increase in coronary flow reserve (+41.2% [IQR: 20.0–61.7] versus −7.8% [IQR: −19.1 to 10.3]; P <0.001). Conclusions: The index of microcirculatory resistance and coronary flow reserve are acutely improved by remote ischemic preconditioning. This raises the possibility that RIPC confers cardioprotection during percutaneous coronary intervention as a result of an improvement in coronary microcirculatory function. Clinical Trial Registration: URL: www.anzctr.org.au/ . Unique identifier: CTRN12616000486426.